Development and in vitro/in vivo evaluation of Zn-pectinate microparticles reinforced with chitosan for the colonic delivery of progesterone. (1st September 2016) - Gadalla, Hytham H.; Soliman, Ghareb M.; Mohammed, Fergany A.; El-Sayed, Ahmed M.
Abstract: The colon is a promising target for drug delivery owing to its long transit time of up to 78 h, which is likely to increase the time available for drug absorption. Progesterone has a short elimination half-life and undergoes extensive first-pass metabolism, which results in very low oral bioavailability (∼25%). To overcome these shortcomings, we developed an oral multiparticulate system for the colonic delivery of progesterone. Zn-pectinate/chitosan microparticles were prepared by ionotropic gelation and characterized for their size, shape, weight, drug entrapment efficiency, mucoadhesion and swelling behavior. The effect of cross-linking pH, cross-linking time and chitosan concentration on progesterone release were also studied. Spherical microparticles having a diameter of 580–720 µm were obtained. Drug entrapment efficiency of ∼75–100% was obtained depending on the microparticle composition. Microparticle mucoadhesive properties were dependent on the pectin concentration, as well as the cross-linking pH. Progesterone release in simulated gastric fluids was minimal (3–9%), followed by burst release at pH 6.8 and a sustained phase at pH 7.4. The in vivo study revealed that the microparticles significantly increased progesterone residence time in the plasma and increased its relative bioavailability to ∼168%, compared to the drug alone. This study confirms the potential of Zn-pectinate/chitosan microparticles as a colon-specific drug delivery system able to enhance the oral bioavailability of progesterone or similar drugs.